Air, earth and underground animals inside the literary work by J. M. Arguedas - Larrú Salazar, Manuel (2011)
In this article we propose to examine the role animals take inside the narrative universe of the work by JMA. Why did the author constantly inserts various beings of nature that concentrates a heavy charge of semantic load? His incorporation is not andean, rather, they possess a meaning and express a certain way of seeing and understanding reality, the same that follows the two systems of the Andean cosmovision: the dual, opposite (hanan-hurin) and complementary (ichoq/allauca); and, the tripartite (hanan pacha/uku pacha/kay pacha). For this purpose, we will appeal to the notion of “Andean historical chronotope” since this theoretical category, developed by Federico Navarrete, will allow us to settle how Arguedas forms the symbolic and social spaces in his work.